The Municipality in Motifs: Batik Marunda as a Reflection of Jakarta’s Modernity - Woelandhary, Ayoeningsih Dyah; Damayanti, Nuning Y; Sunarya, Yan Yan; Adriati, Ira (Journal of Ecohumanism, 2024)
Batik Marunda is among the batik centers that are characterized by the theme of contemporary Jakarta. Therefore, it is important to see how the visual elements in batik shape the concept of the city of Jakarta as the identity of the motif. The aim of this research is to analyze the identity of batik motifs through visual analysis using Kevin Lynch’s theory and visual language. The purpose is to see the potential of the city as a source of inspiration in the development of local batik motifs, with the concept of paths, edges, districts, nodes, and landmarks. Based on the results of the analysis, significant visual elements that represent the image of Jakarta in batik motifs produced by Marunda batik were identified. Analysis on the aspects of visual language in the elements of shape, line, color, composition and texture, is used to translate the aesthetic and representative values of the city image in batik motifs. Methods of research for visual analysis involved field observation, visual documentation and descriptive qualitative data analysis. Results of the study elaborate that the image of Jakarta is formed from elements of the city’s landmark areas, such as buildings, bridges, vegetation and others. Marunda batik motifs illustrate local uniqueness by emphasizing urban elements as its identity. The goal of the present study is to develop local batik that utilizes the potential of the urban environment as a source of creative inspiration, while also serving as a visual chronicle of Jakarta’s municipal growth and transformation.